2013
DOI: 10.1158/1541-7786.mcr-12-0414-t
|View full text |Cite
|
Sign up to set email alerts
|

MYC-Induced Epigenetic Activation of GATA4 in Lung Adenocarcinoma

Abstract: Human lung cancer is a disease with high incidence and accounts for most cancer-related deaths in both men and women. Metastasis is a common event in non-small cell lung carcinoma (NSCLC), diminishing the survival chance of the patients with this type of tumor. It has been shown that MYC is involved in the development of metastasis from NSCLC, but the mechanism underlying this switch remained to be identified. Here, we focus on GATA4 as a MYC target in the development of metastasis with origin in lung adenocar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
(40 reference statements)
1
11
0
Order By: Relevance
“…In contrast, Barbosa et al . showed that GATA4 mRNA expression was more abundant in metastasizing adrenocortical tumors than non‐metastasizing tumors and very recently Castro et al . demonstrated that GATA4 was necessary for MYC‐induced metastasis in lung adenocarcinoma.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In contrast, Barbosa et al . showed that GATA4 mRNA expression was more abundant in metastasizing adrenocortical tumors than non‐metastasizing tumors and very recently Castro et al . demonstrated that GATA4 was necessary for MYC‐induced metastasis in lung adenocarcinoma.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, Hua et al (46) reported that the GATA4 gene was activated by HER2, whereas HER2 expression was repressed by GATA4 through its direct binding to the regulatory sequences, indicating a direct functional link between GATA4 and HER2 in breast carcinoma. In contrast, Barbosa et al (47) showed that GATA4 mRNA expression was more abundant in metastasizing adrenocortical tumors than non-metastasizing tumors and very recently Castro et al (35) demonstrated that GATA4 was necessary for MYC-induced metastasis in lung adenocarcinoma. Therefore, it is suggested that GATA4 is involved in oncogene-dependent signaling including HER2 in the development of distant metastasis with breast carcinoma.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Thus, GATA4 and GATA5 is currently considered potential tumour suppressors, however, GATA6 can be used as a potential oncogene [6]. Altered expression of GATA4, GATA5, and GATA6 are associated with abroad range of tumours emerging from the gastrointestinal tract [50], lungs [51] and brain [52]. Moreover, some studies reported that methylation in the GATA4 and GATA6 promoter region could play an important role in ovarian carcinogenesis, elevated GATA4 and lower GATA6 mRNA levels are associated with better prognosis in ovarian tumours [21,22,25].…”
Section: Discussionmentioning
confidence: 99%
“…The GATA family of transcription factors serve various roles in the process of cell proliferation and differentiation (29,30). The expression of GATA4 has been extensively studied in a number of carcinomas (31)(32)(33)(34). Previous studies have reported that the expression of GATA4 was low in several cancers, including colorectal cancer, adrenocortical tumors, epithelial ovarian cancer and hepatocellular carcinoma, which suggested that GATA4 may serve as a tumor suppressor (35).…”
Section: Discussionmentioning
confidence: 99%